Cross sectional study on the prevalence of polypharmacy and potentially inappropriate medications among elderly patients in a tertiary care centre in central Kerala - Anthoorathodi, Jubina Bency; Joju, Aqueen; Reji, Ann Mereena; Asokan, Anupama Pallivalappil; Naseem, Anzeem; Cherian, Aparna; Sisupalan, Arunima Beena (International Journal Of Community Medicine And Public Health, 2021)
Background: Polypharmacy or the concurrent use of multiple medications, is on the rise, especially in the elderly population as they suffer from multiple co-morbidities. Polypharmacy has been reported to increase the risks for inappropriate medication intake. Objectives: The aim was to investigate the prevalence of polypharmacy and usage of potentially inappropriate medication using Beer’s criteria and to find out the various risk factors of polypharmacy in hospitalised elderly. Methods: A cross sectional study was done in patients aged 60 years and above using a pre designed semi structured questionnaire and from their case records to assess the pattern of polypharmacy by different socio-demographic characteristics and also to found out the risk factors of polypharmacy. Results: 50 patients aged 60 and above were involved in our study out of which, 46% were females and 54% were males. Mean age of our study population was 71.5±8.3. Among them, 30 were hypertensive, 27 were diabetic, 9 of them had dyslipidaemia and 8 of them had coronary artery disease Mean number of medication use was 5.1±4.1. Polypharmacy was observed in 42% of the patients. 20% patients received potentially inappropriate drugs from Beer’s list. We also found significant association of polypharmacy with diabetes mellitus and hypertension. Conclusions: The present study has shown polypharmacy and usage of potentially inappropriate medication as an emerging public health concern. Diabetes mellitus and hypertension were found to be risk factors of polypharmacy. Deprescription should be integrated into clinical care and prescribers need to be educated about Beers criteria and encouraged for rational prescription.